Designing and Developing an Augmented Reality Application: A Sample Of Chemistry Education - Zeynep Taçgın; Nazlıcan Uluçay; Ersin Özüağ (Journal of the Turkish Chemical Society Section C Chemical Education, 2016)
Augmented Reality has been accepted as an effective educational method and this review depends on philosophical background of cognitive science. This means, several channels –aural, visual, and interactivity, etc. - have been used to offer information in order to support individual learning styles. In this study, Natural User Interface- and Human Computer Interaction-based Augmented Reality application has been developed for the chemistry education. The purpose of this study is to design and develop a student-centered Augmented Reality environment to teach periodic table, and atomic structure of the elements and molecules. Head Mounted Display has been used to develop Augmented Reality system, and user control has been executed with hand motions (grab, drag, drop, select and rotate). The hand motion control has been used to improve spatial abilities of students in order to maximize the transferred knowledge. Use of the most common natural controlling tools (fingers and hands) to interact with virtual objects instead of AR markers or other tools provides a more interactive, holistic, social and effective learning environment that authentically reflects the world around them. In this way, learners have an active role, and are not just passive receptors. Correspondingly, the developed NUI-based system has been constructed as design-based research and developed by using instructional design methods and principles to get reach of more effective and productive learning material. Features of this developed material consist of some fundamental components to create more intuitive and conductive tools in order to support Real World collaboration.